Nationalism as political paranoia in Burma An essay on the historical practice of power - Gravers Mikael (Richmond Curzon Press, 1999)
This study probes the complex relationship between nationalism, violence and Buddhism in 19th- and 20th-century Burma. Graver's study examines present-day Burma and the struggle by Nobel Prize winner Aung San Suu Kyi for a new Burmese identity.
Keywords: Nationalism -- Burma -- History. Burma -- Politics and government -- 1824-1948. Burma -- Politics and government -- 1948-